Can Christian ethics be used to engage business? A (South) African consideration - Fourie, Willem (Acta Theologica, 2012)
Business enterprises are in a position to exert a significant influence on society – particularly in the context of developing countries. Businesses no longer simply influence shareholders, employees and customers, but also play a role in strengthening (or weakening) political institutions and contributing to the wellbeing of other stakeholders. The result is that business enterprises are increasingly accountable to a growing number of stakeholders. In this article the possibility of utilising Christian ethics to engage business is investigated. The question is whether it is at all possible for the church to address the business world by applying its particular ethical resources, and – should this be possible – what form such engagements could take.